Lactococcosis a Re-Emerging Disease in Aquaculture: Disease Significant and Phytotherapy - Mehdi Soltani; Bernardo Baldisserotto; Seyed Pezhman Hosseini Shekarabi; Shafigh Shafiei; Masoumeh Bashiri (Veterinary Sciences, 2021)
Lactococcosis, particularly that caused by Lactococcus garvieae, is a major re-emerging bacterial disease seriously affecting the sustainability of aquaculture industry. Medicinal herbs and plants do not have very much in vitro antagonism and in vivo disease resistance towards lactococcosis agents in aquaculture. Most in vitro studies with herbal extractives were performed against L. garvieae with no strong antibacterial activity, but essential oils, especially those that contain thymol or carvacrol, are more effective. The differences exhibited by the bacteriostatic and bactericidal functions for a specific extractive in different studies could be due to different bacterial strains or parts of chemotypes of the same plant. Despite essential oils being shown to have the best anti-L. garvieae activity in in vitro assays, the in vivo bioassays required further study. The extracts tested under in vivo conditions presented moderate efficacy, causing a decrease in mortality in infected animals, probably because they improved immune parameters before challenging tests. This review addressed the efficacy of medicinal herbs to lactococcosis and discussed the presented gaps.